2002
DOI: 10.1073/pnas.052712799
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of striatal and extrastriatal DARPP-32 in biochemical and behavioral effects of fluoxetine (Prozac)

Abstract: Fluoxetine (Prozac) is the most widely prescribed medication for the treatment of depression. Nevertheless, little is known about the molecular basis of its clinical efficacy, apart from the fact that fluoxetine increases the synaptic availability of serotonin. Here we show that, in vivo, fluoxetine, given either acutely or chronically, regulates the phosphorylation state of dopamine-and cAMPregulated phosphoprotein of M r 32,000 (DARPP-32) at multiple sites in prefrontal cortex, hippocampus, and striatum. Acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(136 citation statements)
references
References 37 publications
7
126
1
2
Order By: Relevance
“…Notably, the antidepressant imipramine has an opposite effect as it upregulates AMPA receptors in the hippocampus Gray et al, 2003). These latter results are also consistent with the studies from the Greengard laboratory, demonstrating that chronic fluoxetine significantly enhanced GluR1 phosphorylation (S845) of GluR1 in the hippocampus (Svenningsson et al, 2002).…”
Section: Anticonvulsants As Drugs For Mood Disorders: Diverse Effectssupporting
confidence: 85%
“…Notably, the antidepressant imipramine has an opposite effect as it upregulates AMPA receptors in the hippocampus Gray et al, 2003). These latter results are also consistent with the studies from the Greengard laboratory, demonstrating that chronic fluoxetine significantly enhanced GluR1 phosphorylation (S845) of GluR1 in the hippocampus (Svenningsson et al, 2002).…”
Section: Anticonvulsants As Drugs For Mood Disorders: Diverse Effectssupporting
confidence: 85%
“…Previous studies have shown that drugs that potentiate AMPA currents have antidepressant effects (Li et al, 2001;Knapp et al, 2002). Interestingly, it has also been demonstrated that the antidepressant fluoxetine increases the phosphorylation of GluR1 at Ser 845 in the striatum (Svenningsson et al, 2002), consistent with the possibility that PKA-GluR1 molecular circuits may mediate the antidepressant effects of MCH1R activity in the AcSh.…”
Section: Discussionmentioning
confidence: 60%
“…A recent report indicates that, in addition to DA, 5-HT also regulates DARPP-32 phosphorylation (Svenningsson et al, 2002a), an effect modified by fluoxetine (Svenningsson et al, 2002b). Some of the effects of diverse psychotomimetics on DA, 5-HT, and glutamate activity in humans and in animals appear to be mediated by the DARPP-32 signal transduction pathway (Svenningsson et al, 2003).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%